Development of a Plastic Membrane Containing Micro-hole(s) for a Potential Bio-sensing Application. (2017) - Krikstolaityte, Vida; Ruzgas, Tautgirdas; Heiskanen, Arto; Canali, Chiara; Arnebrant, Thomas; Emnéus, Jenny
Abstract: In this work, a poly (methyl methacrylate) membrane containing micro-holes (MHs) as a prototype of a simple sensing platform of a lab-on-a-chip device has been developed for a potential analysis of clinical fluidic samples. A four probe electrochemical impedance spectroscopy (EIS) setup, with two electrodes placed on each side of the membrane, was adopted for monitoring the MH impedance (Fig. 1a). The setup was used to investigate, if EIS is suitable to sense the trapping of an analyte inside the MHs. Latex micro-beads with a diameter of 10 μm were used to test clogging of the MHs. Additionally, finite element model simulations were performed using Comsol Multiphysics software to theoretically evaluate the sensitivity field of the EIS measurement along the MHs.